Experimental study on practical applications of wearable thermoelectric generator (TEG) - Aziz F.A.; Mohamed H.; Mujaini M. (American Institute of Physics Inc., 2024)
This study aims to investigate the potential applications that can be used for TEG devices. The application that has been used in this project is to light up the LED light bulb by harvesting human body heat using TEG Peltier Module, and the selected and tested human body part is the forehead. Several experiments are conducted on individuals by considering surrounding temperature, skin temperature, input voltage, output voltage, and body mass index (BMI). The values of input and output voltage generated from the TEG and voltage booster are collected and analysed. It is also found that the voltage generated from TEG and voltage booster mostly decreases with the human samples' increment of body mass index. The results also indicate that the checkerboard pattern heat sink produces a slightly higher voltage than the flat plate heat sink with differences only by 0.33mV for initial input voltage and 0.01 V for initial output voltage for a human sample with 18.5 kg/m2 BMI. 2023 AIP Publishing LLC.